Dynamics and structure of project performers of the «Federal target program for research and development in priority areas of development of the Russian scientific and technological complex for 2014–2020» - I. N. Chernova; V. B. Mikhailets; K. V. Shurtakov (Ekonomika Nauki)
The article considers socio-demographic issues of research and development of the «Federal Target Program for Research and Development in Priority Areas of Development of the Russian Scientific and Technological Complex for 2014–2020». Analysis based on project's documents in the Program from 2014 to 2016. We studied the dynamics in both quantitative and qualitative characteristics of project performers – applied research and experimental development, and defined trends of project R&D personnel changes, including sociodemographic characteristics: age, size and composition of performers, the proportion of researchers with academic degree, and the proportion of women-researchers. In the article it is shown that specialists under 40 years of age are the largest part of project performers. The renewal of project personnel in time of projects is 65 percent. In the article it is also shown a strong correlation between project academic personnel and academic personnel of Russia as a whole. We devised proposals for tracking quantitative and qualitative parameters of project performers and for securing growth the skill level of young specialists in projects.